Design of a Multi-Functional Wheelchair Based Fuzzy Analytical Hierarchy Process - Muhammad Nur Iksan; Anita Susilawati (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2021)
Wheelchairs are tools for humans who experience illness, disabilities, and injuries that cause walking difficulties. There are many types of wheelchairs on the market, while wheelchairs that function to help users defecate flexibly have not been widely sold in the market. Therefore, it is necessary to develop a flexible and multifunctional wheelchair that can assist the users in carrying out their activities. This study aims to develop a design of the multifunctional wheelchair. The designing of multifunctional wheelchair based the FAHP (Fuzzy Analytical Hierarchy Process) method. The use of the FAHP was to select the optimal design and selection of the best alternatives among wheelchair’s indicators of design proposed. The results of calculation of weight values for wheelchair design were obtained a percentage of alternative 1 of 48% and alternative 2 of 52%.